The end of white politics : how to heal our liberal divide - Maxwell, Zerlina (Hachette Books, 2020)
"In the entire history of the United States of America, we've never elected a woman as our president. And we've only had one president who was not a white man. After working on two presidential campaigns (for Barack Obama and Hillary Clinton), MSNBC political analyst and SiriusXM host Zerlina Maxwell gained first-hand knowledge of everything liberals have been doing right over the past few elections--and everything they are still doing wrong ... Maxwell argues that it's the "liberal-minded" party's struggle to engage women and communities of color--and its preoccupation with catering to the white, male working class--that threatens to be its most lethal shortfall. The times--and the demographics--are changing, and in order for progressive politics to prevail, we must acknowledge our shortcomings, take ownership of our flaws, and do everything in our power to level the playing field for all Americans"--